2021
DOI: 10.21037/atm-20-5723
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk stratification model for predicting the mortality of acute kidney injury in critical care patients

Abstract: Background: This study aimed to develop and validate a model for mortality risk stratification of intensive care unit (ICU) patients with acute kidney injury (AKI) using the machine learning technique.Methods: Eligible data were extracted from the Medical Information Mart for Intensive Care (MIMIC-III) database. Calibration, discrimination, and risk classification for mortality prediction were evaluated using conventional scoring systems and the new algorithm. A 10-fold cross-validation was performed. The pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…AKI is associated with poor prognosis in patients, including the occurrence of CKD, progression of CKD, prolonged hospital stays, increased adverse cardiovascular events, and mortality ( 28 31 ). Previous studies on predictive models of AKI have mainly focused on specific populations of patients with AKI after cardiac surgery ( 32 , 33 ), AKI after non-cardiac surgery ( 34 , 35 ), septic AKI ( 36 , 37 ), tumor-related AKI ( 38 ), and critical AKI ( 39 ). James et al.…”
Section: Discussionmentioning
confidence: 99%
“…AKI is associated with poor prognosis in patients, including the occurrence of CKD, progression of CKD, prolonged hospital stays, increased adverse cardiovascular events, and mortality ( 28 31 ). Previous studies on predictive models of AKI have mainly focused on specific populations of patients with AKI after cardiac surgery ( 32 , 33 ), AKI after non-cardiac surgery ( 34 , 35 ), septic AKI ( 36 , 37 ), tumor-related AKI ( 38 ), and critical AKI ( 39 ). James et al.…”
Section: Discussionmentioning
confidence: 99%
“…Single- and multiparameter biomarkers (including anion gap, serum calcium, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR)) and scoring systems (including sequential organ failure assessment (SOFA), Acute Physiology and Chronic Health Evaluation II (APACHE II), and simplified acute physiology score II (SAPS II)) have been used in assessing the severity and prognosis of AKI in critically ill patients [ 5 ]. Unfortunately, most of these techniques are unsatisfactory due to low sensitivity or specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and timely prediction of mortality for AKI is required to identify patients at high risk of clinical deterioration so that preventive measures can be taken in a timely manner, which may reduce mortality. Several studies have attempted to establish prognostic models among AKI patients with ML methods and showed a modest prognostic yield [5] , [7] , [8] , [28] , [29] , [30] , [31] , [32] , [33] , [34] . For example, a study from the US constructed a prognostic model for predicting 60-day mortality in critically ill patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, there was a strong correlation between the GCS score and clinical outcome [36] . Nevertheless, none of the previous models included this critical feature in predicting mortality risk for AKI patients [5] , [7] , [8] , [28] , [29] . Our study found that blood urea nitrogen (ranked 2nd) and the cumulative urine output on Day 1 (ranked 3rd) were closely associated with mortality in AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation